Pengenalan Alat Penangkapan Ikan Ramah Lingkungan di Desa Sanahu, Seram Bagian Barat - Ronald Darlly Hukubun; Friesland Tuapetel; Dyah Ayu Prasanthy Aome; Yoseph Mario Dumatubun; Godlife Rojers Umhersuny; Jefry Jefrad Wakim (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
Sanahu Village is a coastal area where most of the residents rely on fisheries as their primary source of livelihood. However, the growing population and increasing economic demands have led to the rise of environmentally unfriendly fishing practices, including the use of gear that damages aquatic habitats. This situation poses a serious threat to the sustainability of marine resources and the balance of coastal ecosystems. Therefore, efforts to provide understanding, education, and guidance to fishermen regarding the importance of using more environmentally friendly fishing gear are urgently needed. The results of the community service activity indicate that socialization on the use of selective fishing gear with minimal negative impact on the ecosystem is highly necessary and has been positively received by the fishermen of Sanahu Village. In addition to increasing awareness, the successful implementation of eco-friendly fishing tools also requires strong support from local government, non-governmental organizations, environmental activists, and active community participation. Such collaboration is essential to establish effective monitoring systems, ensuring that marine resources can be utilized sustainably while preserving the ecological integrity of coastal waters.